Advance Ordering for Healthier Eating? Field Experiments on the Relationship between the Meal Order–Consumption Time Delay and Meal Content. (June 2016) - VanEpps, Eric M.; Downs, Julie S.; Loewenstein, George
Encouraging consumers to select meals in advance rather than at mealtime has been proposed as a strategy to promote healthier eating decisions, taking advantage of the improved self-control that is thought to accompany decisions about the future. In two field studies at an employee cafeteria and a third in a university setting, we examine how time delays between placing a lunch order and picking it up affect the healthfulness of that lunch. The first study, a secondary data analysis, finds that longer delays between placing an order and picking up the meal are associated with reductions in calorie content. The second study tests the causality of this relationship by exogenously restricting some lunch orders to be substantially delayed, leading to a marginally significant (approximately 5%) reduction in calories among delayed orders. The third study compares orders for truly immediate consumption versus orders placed in advance and demonstrates a significant (100 calorie, or approximately 10%) reduction in lunch calories. We discuss evidence regarding possible theoretical mechanisms underlying this effect, as well as practical implications of our findings.